2020
DOI: 10.1016/j.chaos.2020.109866
|View full text |Cite
|
Sign up to set email alerts
|

Development of new hybrid model of discrete wavelet decomposition and autoregressive integrated moving average (ARIMA) models in application to one month forecast the casualties cases of COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
103
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 50 publications
0
103
0
2
Order By: Relevance
“…Besides, recent studies have demonstrated that some hybrid models can also provide a close approximation to the temporal patterns of the COVID-19 outbreak. 50,51 For example, Singh et al proposed a new hybrid model by combining wavelet decomposition and ARIMA model to make forecasting for the total death cases of COVID-19 in Italy, Spain, France, the UK, and the USA. 51 Chakraborty et al developed a novel hybrid ARIMA-wavelet-based forecasting (WBF) model to make real-time forecasts and risk assessment for the morbidity cases of COVID-19 in India, Canada, France, South Korea, and the UK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, recent studies have demonstrated that some hybrid models can also provide a close approximation to the temporal patterns of the COVID-19 outbreak. 50,51 For example, Singh et al proposed a new hybrid model by combining wavelet decomposition and ARIMA model to make forecasting for the total death cases of COVID-19 in Italy, Spain, France, the UK, and the USA. 51 Chakraborty et al developed a novel hybrid ARIMA-wavelet-based forecasting (WBF) model to make real-time forecasts and risk assessment for the morbidity cases of COVID-19 in India, Canada, France, South Korea, and the UK.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 For example, Singh et al proposed a new hybrid model by combining wavelet decomposition and ARIMA model to make forecasting for the total death cases of COVID-19 in Italy, Spain, France, the UK, and the USA. 51 Chakraborty et al developed a novel hybrid ARIMA-wavelet-based forecasting (WBF) model to make real-time forecasts and risk assessment for the morbidity cases of COVID-19 in India, Canada, France, South Korea, and the UK. 50 Therefore, future work is supposed to compare the reliability level in forecasting the epidemiological indicators of the COVID-19 outbreak between the ETS model and the mentioned hybrid techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recommended to extend the lockdown period in case of sharply increase in the number of confirmed cases and deaths. The incorporation between discrete wavelet decomposition and ARIMA to forecast deaths due to COVID-19 in France, Spain, Italy, United Kingdom, and USA was presented by ( Singh et al, 2020 ). The results obtained by the proposed hybrid model reduced the forecasting errors by about 50 % compared with standalone ARIMA model.…”
Section: Introductionmentioning
confidence: 99%
“…This global emergency brings with it important and yet unanswered questions related to the dynamic behavior of the contagion and its mitigation and control strategies. As a result, measures carried out to contain the contagion such as social distancing, quarantine, and complete lock-down of areas have been studied [5] , [6] , [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%